The Mediating Role of Corporate Governance on the Relationship between Accounting Information System and Risk Management: The Case of the Jordanian Industrial Shareholding Companies - Audeh Ahmad Bani Ahmad (STIE Malangkucecwara, 2022)
the primary aim of this study is to examine the mediating effect of corporate governance on the relationship between accounting information system (AIS) and risk management. The population of the study comprised of the entire Jordanian Industrial Shareholding Companies numbering 54. The study objectives were achieved by developing a questionnaire and distributing copies to the employees of the companies accounting departments. Data gathered was analyzed using SPSS 25.0 tool to test the relationships between AIS, corporate governance and risk management. Based on the findings, corporate governance fully mediated the relationship between AIS and risk management in the context of the Jordanian Industrial Shareholding Companies.